Procedures for Cash on Delivery Service Administration at the Bojonegoro Post Office - Gagas Aji; Yanita Alifia Safitri; Maharani Lutfiah Choirun Nisa (Department of Management, Universitas PGRI Yogyakarta., 2023)
Purpose: This research aims to establish the administrative processes used by the PT Pos Indonesia (Persero) Bojonegoro Branch Office, particularly in the delivery administration of products through the cash-on-delivery method. Methodology: This study uses qualitative techniques involving descriptive and explanatory analysis. Observations, interviews, and documentation are used to obtain data to be processed. Qualitative research methods focus on the results of investigations, conclusions, and data collection procedures that combine to convey their significance. Findings: The business process needs to be clarified because no Standard Operating Procedure (SOP) governs the provisions for cash-on-delivery services. This problem might result in material and time losses for couriers, customers, and vendors. Originality: Numerous studies in logistics services have concentrated on the consumer; hence, this study focuses on internal corporate problems. Due to the failure to adhere to standard operating standards, the company's cash-on-delivery operations can be highly complicated. Research limitations: The cash-on-delivery management procedure is the sole topic of this study; neither the employed information system nor the customer satisfaction are examined. In doing so, the corporation hopes to better serve its future customers by capturing internal phenomena.research is reported on in the paper this section must be completed and should include suggestions for future research and any identified limitations in the research process Practical implications: The cash-on-delivery procedure at the Bojonegoro Post may benefit from the standard work solutions derived from this research. Mapping out a workflow can also be interpreted as providing a structure for the business.hat are outcomes and implications for practice? What possible applications and consequences are identified?